Body Mass Index, Dietary Habits and Physical Exercise Among School Going Adolescent: A Cross Sectional Study in Ahmedabad - Shah, Tejas A; Bhatt, Rajshree J; Patel, Mitesh; Patel, Pritesh G (National Journal of Community Medicine, 2013)
Background: The high prevalence of obesity in adolescence is serious public health concern. Longitudinal studies confirm that health consequences of obesity during adolescence track into adulthood and it can be reduced by successfully decreasing body fat among adolescents. Objectives: “The objectives of the study were to assess Body Mass Index of study participants and also to explore their lifestyle like physical exercise, television viewing etc.” Methodology: A cross- sectional study was conducted among randomly selected adolescent students of various secondary and higher secondary schools of Ahmedabad. A pre-tested and pre-designed questionnaire was used to assess the socio demographic variables. BMI was calculated for every student participating in the study. The analysis of data was done using Epi info version-7 software. Results: Out of 112 students participated in the study, as per the BMI 34% students were found to be obese (M=25.7% & F=45.7%) Consumption of junk foods was reported high among boys (66.4%) as compared to girls (33.4%). We found that 57.2% students were spending ≥ 1 hour in watching television. One third of students were not doing any kind of exercise. Conclusion: Marked gender differences were observed in relation to parameters selected for study. Females were found to be comparatively spending more leisure time watching TV/Computer, doing less exercise and having more physical complaints than there male counterpart. This partly explains more obesity prevalent in adolescent females than males.